Suture and Fixation of the Transversalis Fascia during Robotic-Assisted Transabdominal Preperitoneal Hernia Repair to Prevent Seroma Formation after Direct Inguinal Hernia Repair. (June 2021) - Pini, Ramon; Mongelli, Francesco; Proietti, Francesco; Cianfarani, Agnese; Garofalo, Fabio; Di Giuseppe, Matteo; La Regina, Davide
Background. Seroma formation after videoendoscopic repair of inguinal hernias, known as "pseudorecurrence", may vary from an asymptomatic, self-limiting occurrence to a painful, chronic problem. The aim of this study was to investigate the incidence of postoperative seroma in robotic-assisted transabdominal preperitoneal hernia repair (R-TAPP), modified by suturing and fixating the transversalis fascia to the Cooper ligament. Methods. The study was approved by the local ethics committee (2019-01132 CE-3495). Patients undergoing R-TAPP for direct inguinal hernia from October 2017 to December 2019 were included. In all patients, a barbed running suture of the transversalis fascia was performed to close the cavity resulting from the direct hernia reduction and to fix it to the Cooper ligament, then a lightweight mesh was placed. Demographic and clinical data were collected and analysed. Results. Over the study period, 67 R-TAPP in 51 patients were identified. All patients were male, with a mean age of 63.1 ± 12.7 years. There was 1 case of conversion to open surgery due to adhesions of the caecum to the groin as a result of perforated appendicitis. The mean length of the hospital stay was 1.8 ± .6 days. After discharge, no cases of seroma or recurrence at 30 days nor chronic pain at a mean follow-up of 10.3 ± 6.8 months was detected. Conclusions. In the treatment of direct inguinal hernia with R-TAPP, suturing and anchoring the transversalis fascia to the Cooper ligament are safe, feasible and recommendable in order to prevent postoperative seromas.